Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/mop.10502
|View full text |Cite
|
Sign up to set email alerts
|

Application of a 2D‐CFDTD algorithm to the analysis of photonic crystal fibers (PCFs)

Abstract: This research applies an efficient two‐dimensional cylindrical finite‐difference–time‐domain (2D‐CFDTD) algorithm implemented on the transverse plane of a guided‐wave structure to analyze a photonic crystal fiber (PCF) structure. An unsplit anisotropic perfectly matched layer (APML) is used for mesh termination along the radial direction of the PCF. The propagation characteristics of the PCF are analyzed, and excellent agreement is observed between the results derived in this research and those available in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 7 publications
2
21
0
Order By: Relevance
“…The increased light scattering could well be due to the particles hygroscopic growth demonstrated in other studies. For example, Mai et al (2018) found that AODs and SSAs both increased with relative humidity at Guangdong in the Pearl River Delta (PRD) region, which suggests that condensational growth can affect aerosol optical properties.…”
Section: Spatial Distribution Of Aerosol Single-scattering Albedomentioning
confidence: 99%
“…The increased light scattering could well be due to the particles hygroscopic growth demonstrated in other studies. For example, Mai et al (2018) found that AODs and SSAs both increased with relative humidity at Guangdong in the Pearl River Delta (PRD) region, which suggests that condensational growth can affect aerosol optical properties.…”
Section: Spatial Distribution Of Aerosol Single-scattering Albedomentioning
confidence: 99%
“…Land surface energy redistribution includes radiative process and nonradiative process (Burakowski et al, 2018;Burkett & Kusler, 2000;George et al, 2011;Kool et al, 2014;Mahmood et al, 2014). Direct meteorological observations were the most convincing way to illustrate the changes in temperature and other land surface process parameters (Zhang et al, 2002), especially in a very small region. With the development of remote sensing, large amounts of remote sensing data have been applied in the land surface processes related researches from mesoscale to global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion from marshland to CL could reduce albedo by enhancing the vegetation coverage during the growing season (Zhang et al, 2002), but increased albedo because of snow covered after harvesting the crops during the nongrowing season (Lobell et al, 2006). Compared with marshland, CL generally has a smaller ET due to low water content but has a larger ET from July to September (possibly due to strong transpiration from dense planted vegetation) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%